A molecular theory of large-solute diffusion - Yoshimori, A. (Condensed Matter Physics, 2007)
The limit of a large solute in the molecular theory of diffusion developed by Yamaguchi et al. [Yamaguchi T.
et al., J. Chem. Phys., 2005, 123, 034504] is studied. By the limit, the Stokes approximation to the hydrodynamic
equations is derived in the outside region of a diffusing solute. The limit of a large solute also leads to
equations in the inside region of the solute. The analytical solution of the inside equation allows one to derive
the boundary condition, which is needed on the surface of the solute when the hydrodynamic equations
are calculated. The boundary condition includes stick and slip boundary conditions employed by the Stokes
law, in the special case. Besides stick and slip conditions, other conditions can be expressed. The boundary
condition depends on properties of a solvent. Вивчається границя великої розчинюваної частинки в рамках молекулярної теорiї, розвинутої Ямагучi. В цiй границi наближення Стокса до гiдродинамiчних рiвнянь отримано за межами дифузiї розчинюваної частинки. Границя великої частинки також приводить до рiвнянь всерединi областi розчинюваної частинки. Аналiтичний розв’язок дозволяє отримати граничнi умови на поверхнi частинки, необхiднi при розрахунку гiдродинамiчних рiвнянь. Граничнi умови в спецiальному випадку включають граничнi умови змiщення, що використовуються в законi Стокса. Крiм цих, можуть бути отриманi також iншi умови. Граничнi умови залежать вiд властивостей розчинника.